Algoritmos para manejo de cicatrizes - Oliveira, Francisco Felipe Gois De [UNIFESP] (2020)
Introduction: The distinct characteristics of pathological scar patterns must be considered in their approach, hypertrophic scars and keloids require different treatments, in the specialized literature there are several proposed approaches, often based on personal experiences of surgeons. Objective: To discuss the content of Algorithms for the Management of Scars, compiling the information of the instruments, aiming to deepen knowledge about the flowcharts for the prevention and treatment of pathological scars. Methods: Descriptive study of an integrative literature review on algorithms for directing conducts with regard to the prevention and treatment of pathological scars. The was approved by the Research Ethics Committee of UNIFESP. Four Scar Treatment and Prevention algorithms were used: International clinical recommendations on scar management, The Most Current Algorithms for the Treatment and Prevention of Hypertrophic Scars and Keloids, Update on Scar Management: Guidelines for Treating Asian Patients, Updated International Clinical Recommendations on Scar Management: Part 2 - Algorithms for Scar Prevention and Treatment. Results: All algorithms meet the objective of guiding behavior in pathological scars, and were considered good or excellent by the authors. Conclusion: The content of Algorithms for the Management of Scars was analyzed and the authors considered that the information was relevant to guide the prevention and treatment of pathological scars.